Methodology for prioritizing marine environmental pressures under various management scenarios in the Black Sea - Lazar, Luminita; Spanu, Alina; Boicenco, Laura; Oros, Andra; Damir, Nicoleta; Bisinicu, Elena; Abaza, Valeria; Filimon, Adrian; Harcota, George; Marin, Oana; Pantea, Elena; Timofte, Florin; et al. (Frontiers in Marine Science, 2024)
This paper aims to develop a methodology for identifying predominant pressures on the marine ecosystem, underlines the importance of studying these pressures, and highlights the need for management scenarios by investigating how the Black Sea ecosystem responds to the combined effects of increasing human pressures, climate change and policies. The study provides an in-depth analysis of environmental pressures affecting the Romanian Black Sea, emphasising the emerging dominance of physical habitat loss, hydrocarbon introduction, and non-indigenous species invasion. Recent developments, including beach rehabilitation, maritime transport, and oil and gas exploitation, have overshadowed traditional pressures such as nutrient introduction and fishing. The research uses a novel methodological approach to evaluate the implications of these pressures under different Shared Socioeconomic Pathways (SSPs): SSP1 "Taking the Green Road", SSP2 "Middle of the Road", and SSP5 "Taking the Highway". The findings illustrate the complex interplay between economic development and environmental conservation, with each pathway offering distinct outcomes for marine ecosystems. Particularly alarming is the vulnerability of critical habitats to increasing anthropogenic pressures. Our results indicate that even with reduced pressures, the rehabilitation of these ecosystems remains a challenge, underscoring the need for proactive and adaptive management strategies. By considering these scenarios, the research aims to contribute to developing management strategies that promote the sustainability and resilience of the Black Sea ecosystem in the face of ongoing environmental challenges. The findings of this study have implications for policymakers and stakeholders involved in marine management and conservation efforts in the Black Sea region.